230Th and 231Pa on GEOTRACES GA03, the U.S. GEOTRACES North Atlantic transect, and implications for modern and paleoceanographic chemical fluxes. (June 2015) - Hayes, Christopher T.; Anderson, Robert F.; Fleisher, Martin Q.; Huang, Kuo-Fang; Robinson, Laura F.; Lu, Yanbin; Cheng, Hai; Edwards, R. Lawrence; Moran, S. Bradley
Abstract: The long-lived uranium decay products 230 Th and 231 Pa are widely used as quantitative tracers of adsorption to sinking particles (scavenging) in the ocean by exploiting the principles of radioactive disequilibria. Because of their preservation in the Pleistocene sediment record and through largely untested assumptions about their chemical behavior in the water column, the two radionuclides have also been used as proxies for a variety of chemical fluxes in the past ocean. This includes the vertical flux of particulate matter to the seafloor, the lateral flux of insoluble elements to continental margins (boundary scavenging), and the southward flux of water out of the deep North Atlantic. In a section of unprecedented vertical and zonal resolution, the distributions of 230 Th and 231 Pa across the North Atlantic shed light on the marine cycling of these radionuclides and further inform their use as tracers of chemical flux. Enhanced scavenging intensities are observed in benthic layers of resuspended sediments on the eastern and western margins and in a hydrothermal plume emanating from the Mid-Atlantic Ridge. Boundary scavenging is clearly expressed in the water column along a transect between Mauritania and Cape Verde which is used to quantify a bias in sediment fluxes calculated using 230 Th-normalization and to demonstrate enhanced 231 Pa removal from the deep North Atlantic by this mechanism. The influence of deep ocean ventilation that leads to the southward export of 231 Pa is apparent. The 231 Pa/ 230 Th ratio, however, predominantly reflects spatial variability in scavenging intensity, complicating its applicability as a proxy for the Atlantic meridional overturning circulation.